REACTIVE MAGNESIA FROM MAGNESIUM SULFATE HYDRATE: A CIRCULAR ROUTE FOR ACID NEUTRALIZATION SYSTEMS (REMUNOM, 2025)
This work presents an efficient carbothermic route for producing highly reactive magnesium oxide (MgO) from hydrated magnesium sulfate (MgSO₄·H₂O), using charcoal, petroleum coke, and bituminous coal as reducing agents. Experiments conducted in a muffle furnace at 850 °C for 120 minutes yielded MgO in the range of 94.3% to 95.0%. Acid-neutralization tests demonstrated rapid reactivity (44–98 s), and the product exhibited a porous microstructure with particle sizes below 40 µm and low ash content. The process minimizes gypsum waste, enables MgSO₄ recycling, and allows SO₂ capture for sulfuric acid regeneration, offering both environmental and logistical advantages—particularly for sustainable sulfuric-acid-based hydrometallurgical operations in remote regions